NOMADIC AND SEDENTARY LIFE IN THE TIME OF PROPHET MUHAMMAD - Alatas, Alwi; Suleiman, Hassan; Samsudin, Sofiah (Journal of Al-Tamaddun, 2020)
The Bedouins who live nomadically have existed for a long time in the desert region of Arabia. They existed before and during the time of Prophet Muhammad (peace be upon him), when the cities in Arabia were still limited in number and level of population. They led a pastoralist life by herding livestock, especially camels. The Bedouins often appear in stories relating to Prophet Muhammad (pbuh), usually anonymous, with their typical characters of rudeness, discourtasy and lack of knowledge. They came to Makkah and Madīnah from time to time. Sometimes they involved in tribal warfare among themselves or against the emerging Islamic sovereignty. Urban society may play an important socio-political role and has more prominent leadership in the region, but the existence of the Bedouin society cannot be said to be unimportant in the structure of society at that time. Understanding the characteristics and the relation between the Bedouins and the sedentary people is actually important to understand the development of society and civilization, as suggested by the explanation of Ibn Khaldūn in his Muqaddimah. The objective of this study is to elucidate the characteristics of nomadic and sedentary societies and the relationship between the two in the era of the Prophet (pbuh) as well as the Islamic attitude towards these two patterns of life. This research is a historical study that uses the Qur'an and Hadīth as its main sources.